The impact of digital education on household allocation of risky financial assets in China - Ruoxuan Huang; Qinghong Shuai; Yuying Zhang; Yuran Chen; Qiaoyun Zhang (Scientific Reports)
Abstract The digital transformation of education is an inevitable trend, characterized by the deep integration of digital technologies within educational frameworks, making it a crucial driver of educational innovation and reform. Using data from the 2019 China Household Finance Survey, this study empirically examines the effects of digital education on household allocation of risky financial assets, incorporating both mechanistic and heterogeneity analyses. The findings reveal that digital education significantly enhances both the scope and intensity of household engagement with risky financial assets. After addressing endogeneity concerns using instrumental variable techniques and conducting extensive robustness checks, the results consistently validate the initial findings. Furthermore, the impact of digital education on the allocation of risky financial assets varies across different household demographics, with a more pronounced effect observed in households with greater wealth, lower debt ratios, and urban residency. Additionally, the mechanistic analysis clarifies how digital education facilitates the allocation of risky financial assets by broadening access to information, improving financial literacy, and increasing risk tolerance. Overall, this paper underscores the crucial role of digital education in shaping household financial asset allocation.